REFLECTION PHILOSOPHY OF SCIENCE ON THE NORMATIVE STUDY OF MUDHARABAH AGREEMENT FOR STRENGTHENING ISLAMIC EDUCATION - Abdullah, Fadli Daud; Rofiqi, Muhammad Rifqi Lidzikrir; Safitriani, Mida; Nurhasanah, Anne Agnia; Wiwaha, Syahid Mujahid (Prodi Pendidikan Agama Islam STAI Darul Falah, 2026)
This study aims to analyze the legal norms of Islamic economics in the mudharabah contract through the philosophy of science, especially from epistemology, ontology, and axiology, to strengthen the curriculum of Islamic education. This study was conducted with a qualitative descriptive-analytical approach, using primary data from the Qur'an, hadith, DSN-MUI fatwas, and Islamic jurisprudence and legal philosophy literature, which were analyzed using thematic and inductive approaches. The study results indicate that the epistemology of Islamic economic law in the mudharabah contract is built on the integration between revelation and reason through ijtihad, which allows for flexibility and relevance of law to changing times. Ontologically, the mudharabah contract is understood as a manifestation of the values ​​of justice and trust in the Islamic economic system, not just a legal-formal contract. From the axiological side, this contract carries the values ​​of benefit, transparency, and social responsibility. In conclusion, the philosophical approach to the mudharabah contract provides a complete and contextual framework for Islamic education. Hence, it needs to be integrated into the curriculum through critical and applicative learning methods. This study recommends strengthening the competence of teachers or lecturers and compiling teaching materials based on the principles of revelation and the rationality of dynamic Sharia law.